Hubungan Peran Orang Tua Dengan Tingkat Kecemasan Anak Usia Sekolah Yang Mengalami Hospitalisasi Di Murni Teguh Memorial Hospital Medan - Siahaan, Missie Lovely; Tambunan, Dior Manta (STIKes Murni Teguh, 2025)
Illness and hospitalization are often the first crises a child faces. The main stressors of hospitalization are separation, loss of bodily control, and pain. Children's reactions to these crises are influenced by developmental age, previous experiences, and separation. The purpose of this study was to determine whether there is a significant relationship between the role of parents and the level of anxiety of school-age children who were hospitalized at Murni Teguh Memorial Hospital, Medan. This type of research is quantitative research with a cross-sectional study design. The sampling technique in this study was purposive sampling using the Slovin formula, so the sample in this study amounted to 47 respondents. Data analysis used the Spearman Rho test. The results of this study with the Spearman Rho test showed a significant relationship between the role of parents and the level of anxiety of school-age children who were hospitalized at Murni Teguh Memorial Hospital, Medan with a p value = 0.000 (α <0.05) with a correlation coefficient (r) = -0.615, which means the relationship between the two variables is in the strong category. Therefore, it can be concluded that there is a significant relationship between the role of parents and the level of anxiety of school-age children who were hospitalized at Murni Teguh Memorial Hospital, Medan, with the relationship between the two variables in the strong category. As parental involvement increases, anxiety in school-age children experiencing hospitalization decreases. Future research is recommended to include variables related to anxiety in school-age children.